Zebrafish: a novel research tool for cardiac (patho)electrophysiology and ion channel disorders - Verkerk, Arie O.; Remme, Carol Ann (Frontiers in Physiology, 2012)
The zebrafish is a cold-blooded tropical freshwater teleost with a two-chamber heart morphology, typical for non-mammalian vertebrates. A major advantage of the zebrafish for heart studies is that the embryo is transparent, allowing for easy assessment of heart development, heart rate analysis and phenotypic characterization. Moreover, rapid and effective gene-specific knockdown can be achieved using morpholino oligonucleotides. Lastly, zebrafish are small in size, are easy to maintain and house, grow fast, and have large offspring size, making them a cost-efficient research model. Zebrafish embryonic and adult heart rates as well as action potential shape and duration and electrocardiogram morphology closely resemble those of humans. However, whether the zebrafish is truly an attractive alternative model for human cardiac electrophysiology depends on the presence and gating properties of the various ion channels in the zebrafish heart, but studies into the latter are as yet limited. The rapid component of the delayed rectifier K+ current (IKr) remains the best characterized and validated ion current in zebrafish myocytes, and zebrafish may represent a valuable model to investigate human IKr channel related disease, including long QT syndrome. Arguments against the use of zebrafish as model for human cardiac (patho)electrophysiology include its cold-bloodedness and two-chamber heart morphology, absence of t-tubuli, sarcoplamatic reticulum function, and a different profile of various depolarizing and repolarizing ion channels, including a limited Na+ current density. Based on the currently available literature, we propose that zebrafish may constitute a relevant research model for investigating ion channel disorders associated with abnormal repolarization, but may be less suitable for studying depolarization disorders or Ca2+-modulated arrhythmias.